Unraveling gene regulation mechanisms in fish: insights into multistress responses and mitigation through iron nanoparticles - Kumar, Neeraj; Thorat, Supriya Tukaram; Gunaware, Meghana Ajit; Kumar, Paritosh; Reddy, Kotha Sammi (Frontiers in Immunology, 2024)
The recent trend of global warming poses a significant threat to ecosystems worldwide. This global climate change has also impacted pollution levels in aquatic ecosystems, subsequently affecting human health. To address these issues, an experiment was conducted to investigate the mitigating effects of iron nanoparticles (Fe-NPs) on arsenic and ammonia toxicity, as well as high-temperature stress (As+NH3+T). Fe-NPs were biologically synthesized using fish waste and incorporated into feed formulations at concentrations of 10, 15, and 20 mg kg-1 diet. Twelve treatments were designed in triplicate following a completely randomized design, involving a 540 fish. Fe-NPs at 15 mg kg-1 diet notably reduced cortisol levels in fish exposed to multiple stressors. Gene expressions of HSP 70, DNA damage-inducible protein (DDIP), and DNA damage were upregulated by stressors (As+NH3+T) and downregulated by Fe-NPs. Apoptotic genes (Cas 3a and 3b) and detoxifying genes (CYP 450), metallothionein (MT), and inducible nitric oxide synthase (iNOS) were downregulated by Fe-NPs at 15 mg kg-1 diet in fish subjected to As+NH3+T stress. Immune-related genes such as tumor necrosis factor (TNFα), immunoglobulin (Ig), and interleukin (IL) were upregulated by Fe-NPs, indicating enhanced immunity in fish under As+NH3+T stress. Conversely, toll-like receptor (TLR) expression was notably downregulated by Fe-NPs at 15 mg kg-1 diet in fish under As+NH3+T stress. Immunological attributes such as nitro blue tetrazolium chloride, total protein, albumin, globulin, A:G ratio, and myeloperoxidase (MPO) were improved by dietary Fe-NPs at 15 mg kg-1 diet in fish, regardless of stressors. Antioxidant genes (CAT, SOD, and GPx) were also strengthened by Fe-NPs in fish. Genes associated with growth performance such as growth hormone regulator (GHR1 and GHRβ), growth hormone (GH), insulin-like growth factor (IGF 1X and IGF 2X) were upregulated, enhancing fish growth under stress, while SMT and MYST were downregulated by Fe-NPs in the diet. Various growth performance indicators were improved by dietary Fe-NPs at 15 mg kg-1 diet. Notably, Fe-NPs also enhanced arsenic detoxification and reduced cumulative mortality after bacterial infection. In conclusion, this study highlights that dietary Fe-NPs can effectively mitigate arsenic and ammonia toxicity as well as high-temperature stress by modulating gene expression in fish.